The Democratization of Luxury Products with Influencer Marketing - Kalender, Gulcin Ipek (Archives of Business Research, 2021)
Female influencers, who are enthusiastic about disclosing their lifestyles to the masses on social media on topics ranging from giving personal skin care to themselves at their homes to matching different outfits and creating combinations for date nights as the latest fashionistas, to preparing diet and healthy meals for having a fit body shape, or showing how to exercise to have a balanced work-out, try to change the lifestyle habits and the conversation topics in the lives of many young people by presenting themselves as opinion leaders, view affecters or digital penetrators (Deniz, 2021, p. 49). Lifestyle influencers who prepare make-up tutorials in which they set the new trends by also adding parts from their own lives such as going shopping and purchasing different outfits, and going for a meeting with a group of friends at a restaurant with a luxurious product such as a bag, not only help the dissemination of brand awareness, but also motivate young people to try new masstige products by inciting them to hedonic shopping. Many lifestyle influencers are fond of luxury products and they prepare vlogs in which they open a special luxury product such as a bag and this can be named as a transformation of luxury products because these special goods that address to the elite become visibly available to the masses through social media, which is a populous tool. This research aims to show what influencer marketing is in fact about and how influencer marketing creates brand awareness of luxury products by showing these products as a part of influencers’ lifestyle. The results show that influencers’ introduction of luxury products on social media helps the democratization process of luxury products.